Analisis Pengaruh Roa, NPL dan BI Rate Terhadap Penyaluran Kredit di Industri Perbankan Periode Tahun 2015-2019 - M. Isra Arlmal Fayaupon (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to analyze the effect of Return On Assets (ROA), Non Performing Loans, and BI Rate on lending. The research population includes all conventional commercial banks in Indonesia. The data analysis method used is panel data regression with a random effect model. The research period used is monthly from January to December 2015-2019. This research was conducted by taking secondary data from the publication of the Financial Services Authority (www.ojk.go.id). The results of this study indicate that (1) ROA has an insignificant negative effect on lending to commercial banks of 0.495 (2) NPL has a positive and insignificant effect on lending to commercial banks of 0.200, (3) Bi Rate has a significant positive effect on lending to commercial banks is 0.0034. (6) Simultaneously Roa, NPL, and BI Rate have a significant effect on lending to commercial banks with an F-statistical probability value of 0.030598.